The prevalence of alternative herbal medicine and nutritional complementary product intake in patients admitted to out-patient cardiology departments - Esra Gücük İpek; Yeşim Güray; Burcu Demirkan; Ümit Güray; Habibe Kafes; Funda Başyiğit (KARE Publishing, 2013)
Objectives: To detect the prevalence of alternative herbal medicine and nutritional complementary product intake in patients admitted to outpatient cardiology clinics and to determine demographic characteristics, comorbidities and medical properties of those patients. Study design: Patients admitted to outpatient cardiology clinics between June 2011 and March 2012 were given questionnaires involving age, gender, education, occupation, chronic illness, medication, herbs, nutritional complementary products, the index purpose and motivation for using herbs and nutritional complementary products. The data of those questionnaires were analyzed. Results: A total of 454 questionnaires were collected. The mean age was 49+-13 and 48% of the participants were female. Of those patients, 12% had diabetes, 34% had hypertension, 26% had coronary artery disease, 7% had heart failure, 58% had chronic illness, 49% had cardiovascular disease, and 57% had history of drug intake. Including vitamins and minerals, there were 75 (16%) patients taking alternative and complementary medicine. When vitamins and minerals were excluded, 56 (12%) patients were using at least one product, while 24 (5%) patients were using more than one. Garlic (n=33), flaxseed (n=13), ginger (n=12), omega 3 (n=12), and turmeric (n=11) were the most popular products. Of those 56 patients, 32% were using alternative medicine for hypertension and 23% for hyperlipidemia treatment, while 20% were using those products to be healthier in general. Alternative medicine was more prominent in females (p=0.04), and older patients (p=0.004). Education level, drug intake, and the presence of chronic illnesses, hypertension and cardiovascular disease were significantly higher in those patients. Conclusion: Alternative and complementary products were common in patients admitted to outpatient cardiology clinics. Female gender, advanced age, higher education level, drug intake, and having a chronic illness were predisposing factors.